EFFECTS OF AN AXIAL MAGNETIC-FIELD ON THE GROWTH INTERFACES IN VERTICAL GRADIENT FREEZE GAAS CRYSTAL-GROWTH - PARK, YJ; KIM, EK; SON, MH; MIN, SK (ELSEVIER SCIENCE BV, 1995)
The effects of the axial magnetic field on the growth striations of vertical gradient freeze GaAs have been studied. It is shown that the application of an axial magnetic field can afford to a perfect single crystal without any twin formations. For the crystal with zero magnetic field, the striations are irregularly spaced in the conical region and are mainly dependent on irregular facet evolutions. However, the growth interface becomes straighter and flatter compared to that of the crystal with B = 0 when the magnetic flux density is increased to 1200 G. Irregularities of the facet evolution existing in the conical region of the crystal with zero magnetic field are almost eliminated by the application of an axial magnetic field.
Keywords: DISLOCATION